Morphometric traits in the fine-leaved fescues depend on ploidy level: the case of Festuca amethystina L. - Agnieszka Rewicz; Przemysław Piotr Tomczyk; Marcin Kiedrzyński; Katarzyna Maria Zielińska; Iwona Jędrzejczyk; Monika Rewers; Edyta Kiedrzyńska; Tomasz Rewicz (PeerJ, 2018)
Background Polyploid specimens are usually characterized by greater exuberance: they reach larger sizes and/or have a larger number of some organs. Festuca amethystina L. belongs to the section Aulaxyper. Based on morphological features, four subspecies of F. amethystina have been already identified. On the other hand, it has two cytotypes: diploid and tetraploid. The main aim of our study was to distinguish morphological differences between the cytotypes of F. amethystina, assuming that its phenotype differs significantly. Methods The nuclear DNA content was measured by flow cytometry in dry leaves from specimens originating from 13 populations of F. amethystina. Several macrometric and micrometric traits of stems, spikelets and leaf blades were taken into account in the comparative analysis of two cytotypes. Results In the case of cytotypes, specimens of tetraploids were larger than diploids. The conducted morphometric analysis of leaf cross-sections showed significant differences between the cytotypes. Discussion The research has confirmed for the first time that in the case of F. amethystina the principle of greater exuberance of polyploids is true. Differences between the cytotypes are statistically significant, however, they are not enough to make easy the distinction of cytotypes on the basis of the measurements themselves. Our findings favor the rule known in Festuca taxonomy as a whole, i.e. that the ploidy level can be one of the main classification criteria.